Reactive Oxygen Species Modulate Th17/Treg Balance in Chlamydia psittaci Pneumonia via NLRP3/IL-1β/Caspase-1 Pathway Differentiation - Jiang, Rong; Zhou, Haibo; Kong, Xianglong; Zhou, Zhiguo (Folia biologica, 2024)
Chlamydia psittaci pneumonia (CPP) is a lung disease caused by the infection with the Chla-mydia psittaci bacterium, which can lead to severe acute respiratory distress syndrome and systemic symptoms. This study explored the specific mechanisms underlying the impact of reactive oxygen species (ROS) on the Th17/Treg balance in CPP. The levels of ROS and the differentiation ratio of Th17/Treg in the peripheral blood of healthy individuals and CPP patients were measured using ELISA and flow cytometry, respectively. The association between the ROS levels and Th17/Treg was assessed using Pearson correlation analysis. The ROS levels and the Th17/Treg ratio were measured in CD4+ T cells following H2O2 treatment and NLRP3 inhibition. The effects of H2O2 treatment and NLRP3 inhibition on the NLRP3/IL-1β/caspase-1 pathway were observed using immunoblotting. Compared to the healthy group, the CPP group exhibited increased levels of ROS in the peripheral blood, an elevated ratio of Th17 differentiation, and a decreased ratio of Treg differentiation. ROS levels were positively correlated with the Th17 cell proportion but negatively correlated with the Treg cell proportion. The ROS levels and NLRP3/IL-1β/caspase-1 expression were up-regulated in CD4+ T cells after H2O2 treatment. Furthermore, there was an increase in Th17 differentiation and a decrease in Treg differentiation. Conversely, the NLRP3/IL-1β/caspase-1 pathway inhibition reversed the effects of H2O2 treatment, with no significant change in the ROS levels. ROS regulates the Th17/Treg balance in CPP, possibly through the NLRP3/IL-1β/caspase-1 pathway. This study provides a new perspective on the development of immunotherapy for CPP.
Keywords: buněčná diferenciace; signální transdukce; Signal Transduction; reaktivní formy kyslíku; Interleukin-1beta; Humans; Chlamydophila psittaci; lidé středního věku; NLR Family, Pyrin Domain-Containing 3 Protein; Th17 Cells; Psittacosis; protein NLRP3; Female; dospělí; NLRP3/IL-1β/Caspase-1; ROS; lidé; Th17/Treg; Reactive Oxygen Species; kaspasa 1; CD4+ T cells; Adult; ženské pohlaví; psitakóza; Male; Middle Aged; peroxid vodíku; interleukin-1beta; buňky Th17; Cell Differentiation; regulační T-lymfocyty; T-Lymphocytes, Regulatory; mužské pohlaví; Caspase 1; Hydrogen Peroxide; CPP